Public Support for the Euro Essays on Labor Productivity, Monetary Economics, and Political Economy, Vol. 2 - Roth, Felix (Contributions to Economics, 2022)
The long-term sustainability of the euro and the Economic and Monetary Union (EMU) depends heavily on their ability to attract widespread public support. The public support shown for the euro throughout its first three decades has helped to shield it against populist attempts at the national level to dismantle the common currency. It has granted political legitimacy to the presidents of the European Central Bank to do "whatever it takes" when the euro has faced a crisis. Public Support for the Euro is the second of two Open Access volumes presenting a selection of the author's essays on Labor Productivity, Monetary Economics, and the Political Economy, which represent the second part of his habilitation in economics. This second volume brings together eleven of the author's essays, selected with a view to provide an overview of the evolution of his research on public support for and the economics and the political economy of the euro and EMU. .